Efektivitas Strategic Hope - focused Marital Enrichment untuk Peningkatan Penyesuaian Pernikahan Pasangan yang Menikah Melalui Ta'aruf - Zulfa Febriani; Augustine R. Basri; Dini Rahma Bintari (Universitas Islam Indonesia, 2010)
Strategic hope-focused marital enrichment is on brief marital enrichment program with an eclectic approach that focused on increasing love, faith and the importance of working together as a couple to motivate couple in increasing their relationship's quality (Jakubowski, Milne, Brunner, and Miller,2004). The program improved marital relationship, communication, maritalsatisfaction(Worthington Jr., Hight, Ripley, etal, 1997) and overall quality of life (Buchard, Yarhouse, Killian, Worthington Jr., 2003). Rumondor (2010) had adopted the program on newlywed-couples that experienced dating before. This research is to test the effetivity of the program to three ta'aruf-married couples in their beginning phase of marriage. The participants attended four sessions for about a month. The quality of marital adjustment is measured by Dyadic Adjustment Scale (DAS), developed by Spanier (1976). The average total score of DAS in three couples showed an increasing on marital adjustment quality at the end of the program. The program increases dyadic consensus, dyadic satisfaction and affectionai expression meanwhile does not show any difference on dyadic cohesion.Keywords: Marital enrichment, marital adjustment, beginning phase of marriage, ta'aruf